(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Electric vehicles are becoming more and more popular due to their environmental benefits and lesser operating cost. However, the main challenges related with EV’s are lengthy time charging required. This abstract proposes a novel approach to address this challenge by developing a solar-powered charging system in EV’s. that is fast and efficient. DAB converters are used to transfer power from a solar photovoltaic (PV) system to the EV battery. An (ANFIS) controller will be used to enhance the act of the DAB converter, ensuring that the control is moved in solar panels to the battery. The arrangement is designed to reach a 75% charge for a lithium-ion battery in 50 minutes using a Dual active bridge and an ANFIS controller. This represents a significant improvement over conventional charging methods, which can take several hours to fully charging an EV battery. The system will be modelled and simulated using MATLAB SIMULINK. The system can operate efficiently even under disturbances and fluctuations. These findings suggest that wireless charging has the potential to become a viable alternative to conventional charging methods.